PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 006 RAJA BEJAMU KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Kalsum Kalsum; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstratc: This research is motivated by the fact that science student learning outcomes appear to be low and there are still many student who have reached the KKM. Of the 25 student only 12 students (48%) , which reached in Class IV SD Negeri 006 Raja Bejamu. Research instruments consisted of a learning Tool used in this research is guided by the Education Unit Level Curriculum (SBC), known as Curriculum 2006 learning device consists of a syllabus, lesson plans, student worksheets and observation sheet. The first meeting for the first cycle of activity the teachers with an average teacher activity was observed on the second cycle increased compared with the cycle I. At the first meeting I cycle average teacher activity 79,2% in category good, at the second meeting of the average activity teachers increased to 83,3% also in the category of good. At the third meeting of the second cycle the average activity of 87,5% of teachers with very good category and the fourth meeting with an average activity of 91,7% in category very good. Thie first meeting of the first cycle an average 79,2% of student activity with good categaries, at the second meeting of the average activity increased to 87,5% in very good categories. At the third meeting of the second cycle an average of 87,5% of student activity in the very good category and the fourth meeting increased compared with the previous meeting by an average of 91,7% of student activity with very good category. Student learning outcomes after initial data of students worth over KKM only 12 people (48%) after the first cycle an increase of up to 15 people (60%) after the second cycle to be increased up to 21 people (84%). Similarly the average value average student classically obtained at baseline and after just 57,56 and I cycle to increase by an average of 63,60 and in the second cycle to be increased to 74,6. This means that the classical value obtained student has above KKM has been determined.Keywords: Learning Model of Student Teams Acvievement Divisions (STAD),learning outcomes IPS